Rashba exciton in a 2D perovskite quantum dot. Issue 39 (4th October 2021) - Swift, Michael W.; Lyons, John L.; Efros, Alexander L.; Sercel, Peter C.
Abstract : "Rashba excitons" in 2D perovskites have dispersion minima at non-zero quasimomenta. Implications to bright and dark confined excitons are presented. Abstract : The Rashba effect has been proposed to give rise to a bright exciton ground state in halide perovskite nanocrystals (NCs), resulting in very fast radiative recombination at room temperature and extremely fast radiative recombination at low temperature. In this paper we find the dispersion of the "Rashba exciton", i.e., the exciton whose bulk dispersion reflects large spin–orbit Rashba terms in the conduction and valence bands and thus has minima at non-zero quasi-momenta. Placing Rashba excitonsin quasi-2D cylindrical quantum dots, we calculate size-dependent levels of confined excitons and their oscillator transition strengths. We consider the implications of this model for two-dimensional hybrid organic–inorganic perovskites, discuss generalizations of this model to 3D NCs, and establish criteria under which a bright ground exciton state could be realized.